2011
DOI: 10.1038/pcan.2011.42
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative weight change and risk of adverse outcome following radical prostatectomy: results from the Shared Equal Access Regional Cancer Hospital database

Abstract: BACKGROUND:We examined the relationship between weight change in the year before radical prostatectomy (RP) and biochemical recurrence (BCR) and adverse pathology. METHODS:We abstracted data from 359 men undergoing RP in the SEARCH (Shared Equal Access Regional Cancer Hospital) database between [2001][2002][2003][2004][2005][2006][2007]. Logistic regression and Cox proportional hazards models were used to test the association between weight change in the year before surgery and adverse pathology and BCR, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 25 publications
2
13
1
Order By: Relevance
“…Several previous studies have reported a positive association between obesity at time of diagnosis or time of treatment and risk for biochemical recurrence . However, the few existing studies that have examined the association of pre‐diagnostic weight gain and biochemical recurrence have reported inconsistent results . In accordance with our findings, among a cohort of men treated with radical prostatectomy, Strom et al .…”
Section: Discussionsupporting
confidence: 90%
“…Several previous studies have reported a positive association between obesity at time of diagnosis or time of treatment and risk for biochemical recurrence . However, the few existing studies that have examined the association of pre‐diagnostic weight gain and biochemical recurrence have reported inconsistent results . In accordance with our findings, among a cohort of men treated with radical prostatectomy, Strom et al .…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, some large prospective cohort studies have reported that weight gain in adulthood is associated with increased prostate cancer-specific mortality (Bassett et al 2011; Wright et al 2007), although others reported no association between adult weight change and prostate cancer-specific mortality (Chamberlain, et al 2011; Moller, et al 2013). Studies focused on weight change within the decade of prostate cancer diagnosis report more consistent findings, with weight gain in the five year time period preceding diagnosis associated with increased risk of recurrence (Joshu, et al 2011; Whitley, et al 2011), and weight gain in the five year time period following diagnosis associated with increased risk of prostate cancer-specific mortality (Bonn, et al 2014). …”
Section: Obesity and Related Co-morbidities As Modifiable Lifestylmentioning
confidence: 90%
“…20 The database included information on the patients’ age at the time of bone scan, race, height, weight, preoperative PSA levels, surgical specimen pathology (specimen weight, tumor grade, stage and surgical margin status), follow-up PSA, bone scans and secondary treatments after surgery. Patients treated with preoperative ADT or radiotherapy were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%